Green City Hotel of Surakarta - Ramadhina, Fitria Gita; , Dr.Ir.Dhani Mutiari,MT; , Ir. Samsudin Raidi, Msc (2016)
Solo city tourism development is increasing every year. Solo city center and economic potential as a business because it is supported by the geographical position as a link three (3) major cities such as Yogyakarta, Surabaya, Semarang and full modes of transportation to get to the city of Solo, such as railway stations and the international airport Adisumarmo. The development of the construction of hotels in Solo increasing, with responses from the issue of global warming and the reduction of green land in the city of Solo. So the design of a city hotel brings the concept of green architecture. By minimizing the negative impact of buildings on the design of nature, the environment and humans. Reduction in green areas in the city were replaced by buildings, so it is necessary to put the public green space into the building as an alternative communal space. Final of the planning process is the following problem formulation: "How to create a Green City Hotel of Surakarta be able to become a building five-star hotel with the implementation of Green Architecture, which provides special facilities in terms of the convention, as well as be able to apply the cultural nuances of Solo into the building, it will make a difference with hotels another in the city of Solo " The issues raised: 1. Alternative Site Location 2. The concept of Green Architecture. 3. The concept of Space Flexibility Convention 4. How to plan a hotel with a cultural atmosphere Surakarta (Atmosphere is referred to in terms of interior) For buildings using modern concepts. Therefore, the author had the idea to create a tourist accommodation that has the concept of Green architecture with emphasis on five aspects, namely conserving energy, Working With Climate, Respect For Site, Respect For Users, Limmiting New Resource. In addition to the concept of green architecture, this five-star hotel also has facilities that convention 15 meeting rooms, one room rental, two ballrooms that can be incorporated and recreation areas as container activities of citizens. Understanding the title of Green City Hotel of Surakarta is "A tourism accommodation facilities in the city with a stay, business, or on vacation with the concept of green architecture in harmony with the face of the city of Solo. In consideration of the theme Solo environmentally friendly towards the realization of eco-cultural city. Eco Cultural City is a concept of building a city with the feel of the culture and environment-friendly city.